Fundamental solutions to enhance the efficiency of managing soft skills education for current pedagogical students - Nguyen Thi Yen Ngoc (Journal of State Management, 2024)
Faced with the demands and challenges of integration, the workforce in general and pedagogical students in particular need to be trained in skills, especially soft skills, to effectively manage their work, maintain sustainable employment, adapt to modern life, and thrive in an increasingly dynamic, pressured, and competitive environment. A current issue is how to improve the quality of soft skills education management for pedagogical students. Based on a survey of the management of soft skills education for pedagogical students at several universities, the author proposes several fundamental solutions to enhance the efficiency of managing soft skills education for pedagogical students in Vietnam today.